Evaluation of a Rapid Dengue ICT Test in Comparison to PCR for Early Detection of Dengue Serotype in Bangladesh (Pulse, 2026)
Background: Dengue virus infection is one of the major public health concerns in Bangladesh. Recently, dengue is drastically spread out in all main cities as well as rural areas. There are four serotypes of dengue virus, and their existence were already reported in Bangladesh. Dengue severity and fatal outcomes are increasing, probably due to secondary infection by a different serotype of dengue virus than the first infection. So, it is equally important to identify serotypes along with dengue virus detection.Objectives: In this study, we evaluated a newly developed NS1 based Rapid ICT dengue serotype kit for the determination of dengue serotype in Bangladesh patients.Methodology: A total of 98 known Dengue NS1 positive serum samples were tested with the newly developed ICT based Dengue serotype specific NS1 test kit (Osaka University, Japan). The serotype results were compared with the commercial Genesig (PrimerDesign, UK) one step reverse transcriptase real time PCR kit.Results: Out of the 98 samples studied, 78 (79.59%) were tested positive using Dengue ICT-based serotype kit. Of these positive samples, 52 (66.67%) were identified as DENV-2, 21(26.92%) as DENV-3, 3 (3.85%) as DENV-4 and 2(2.56%) were co-infections with DENV-2 and DENV-3. On the other hand, by PCR serotype kit, we found 79 (80.61%) positive cases of which serotype of 73 (74.49%) cases showed concordance results with ICT kit. These results demonstrate that the new Dengue ICT-kit has a high serotype specificity with the PCR serotype kit, although the detection sensitivity of both these serotype kits is somewhat lower than the SD biosensor Dengue NS1 ICT kit.Conclusion: Thus, this kit may help our community to diagnose dengue with its serotype, especially in district and rural areas where PCR laboratory facilities are not available.Pulse Volume 17, Issue 2 2025; 10-14